CONTRIBUIÇÕES DA GESTÃO ESTRATÉGICA DE PESSOAS PARA A SUSTENTABILIDADE ORGANIZACIONAL EM UMA INDÚSTRIA DE PAPEL DO ESTADO DO PARANÁ - Zaias, Luciane Jose da Luz (2019)
This study was developed based on strategic people management aligned with organizational sustainability. Since the organizations constantly seek institutional success, people management has been considered extremely important for the companies, as the staff is the human capital of the organization. In addition to contributing significantly to the corporate success, the practices and policies of people management can collaborate with organizational sustainability. In this context, the issue of this research was to analyze how the practices of people management are related with the pillars of organizational sustainability in a paper industry located in Paraná state. The general objective of this research was to identify and analyze the relations among the practices of people management and the pillars of organizational sustainability. The theoretical reference presented concepts about strategic people management, people management practices, which were highlighted in recent studies, and organizational sustainability. The research was applied to the employees of paper industry, and was characterized as a descriptive study with quantitative approach. The data collection was held through questionnaires, with the participation of 236 employees. Statistical analysis using the software Statistical Package for the Social Science (SPSS), descriptive statistical analysis, Cronbach’s Alfa, factorial analysis, correlation among the variables and regression were carried out. The results showed that the policies and practices of people management, adopted by the organization, are related to the three pillars of organizational sustainability: economic, social and environmental. From the statistical results obtained, it was possible to infer that the employees of industry notice four practices of people management: Recruitment and Selection, Training and Development, Rewards and Performance Evaluation, which are related to the pillars of organizational sustainability; among these practices, the first two are significant, showing the concern of the company in training its employees to perform their functions. It is noticeable that industry studied has been seeking to strengthen this alignment between strategic people management and organizational sustainability, aiming at their objectives, through control and commitment. It has been found that the research can contribute to the industry, concerned in the sense of identifying which practices in people management have greater relation to the practices related to the pillars of organizational sustainability. With limitation in the study, the fact that this research was carried out in only one industry was verified, therefore, for further studies, the implementation of the research in more than one industry is suggested, with the purpose of identifying the existing relations.